2014
DOI: 10.1007/s00411-014-0514-0
|View full text |Cite
|
Sign up to set email alerts
|

The RABiT: high-throughput technology for assessing global DSB repair

Abstract: At the Center for High-Throughput Minimally Invasive Radiation Biodosimetry we have developed a Rapid Automated Biodosimetry Tool (RABiT); this is a completely automated, ultra-high throughput robotically-based biodosimetry workstation designed for use following a large scale radiological event, to perform radiation biodosimetry measurements based on a fingerstick blood sample. High throughput is achieved through purpose built robotics, sample handling in filter-bottomed multi-well plates and innovations in hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 42 publications
0
37
0
1
Order By: Relevance
“…The RABiT ( R apid A utomated Bi odosimetry T echnology) approach for (among other endpoints) high-throughput γ-H2AX measurements was initially developed as an ultra-high-throughput technology for biodosi-metric reconstruction of past radiation exposures, measuring micro-nucleus or γ-H2AX yields in a fingerstick of blood, with a throughput of ~30,000 samples per day [21]. This fully-automated high-throughput methodology has been adapted to assay global DRC through automated quantification of the time-dependent kinetics of the disappearance of γ-H2AX foci after a radiation challenge [22]. …”
Section: Tools and Technologies In Dna Damage Repair And Mutagenementioning
confidence: 99%
See 2 more Smart Citations
“…The RABiT ( R apid A utomated Bi odosimetry T echnology) approach for (among other endpoints) high-throughput γ-H2AX measurements was initially developed as an ultra-high-throughput technology for biodosi-metric reconstruction of past radiation exposures, measuring micro-nucleus or γ-H2AX yields in a fingerstick of blood, with a throughput of ~30,000 samples per day [21]. This fully-automated high-throughput methodology has been adapted to assay global DRC through automated quantification of the time-dependent kinetics of the disappearance of γ-H2AX foci after a radiation challenge [22]. …”
Section: Tools and Technologies In Dna Damage Repair And Mutagenementioning
confidence: 99%
“…A key aspect here is the use of a small, inexpensive automated capillary fingerstick irradiator [22]. The multi-well plates containing the cells are maintained in the RABiT incubator, and the post-irradiation, time-dependent γ-H2AX yield measurements are based on sequential automated samplings from these lymphocytes at five post-irradiation times from 0.5 to 24 h. A typical result from a study of 94 individuals is shown in Fig.…”
Section: Tools and Technologies In Dna Damage Repair And Mutagenementioning
confidence: 99%
See 1 more Smart Citation
“…An automated biodosimetry tool with high throughput was developed for use following large-scale radiological events on the basis of measurements of fingerstick blood samples. Attempts were presented to extend this tool to measure the kinetics of DNA repair proteins like c-H2AX (Turner et al 2014).…”
Section: Retrospective Dosimetry For Mass Casualty Eventsmentioning
confidence: 99%
“…An assay for quantifying DNA repair kinetics (28,29) was also developed (under NIEHS funding) by modifying the gamma-H2AX RABiT assay. In the modified assay, an irradiated sample is split and analyzed at multiple time points post irradiation, generating a curve as seen in Figure 4.…”
Section: New Cytogenetic Assaysmentioning
confidence: 99%